Institutional Change in Southeast Asia - Sjöholm, Frederik; Tongzon, José (European Institute of Japanese Studies East Asian Economics and Business Series, 2005)
This book examines the institutional changes taking place in, and challenges facing, the region since 1997. It also describes various differences in the reform process between countries in the region. Sjöholm and Tongzon argue that the economies of southeast Asia need to reform their institutions if the previous rapid development is to continue. The institutional weaknesses have been addressed to different degrees and with different success in the affected countries. Against the backdrop of southeast Asia's importance in the world economy, it is hardly possible to overestimate the need to understand this process of change.